Group exercises for addiction counseling - Miller, Geraldine A., 1955- (Hoboken, N.J. : John Wiley and Sons, 2012)
"Created to meet the unique needs of addiction professionals, this practical resource offers suggestions for effectively using activities in groups. It addresses common issues counselors frequently need to discuss with clients and provides an array of "tried and true" techniques and exercises designed to help clients develop interpersonal relationship skills and the individual awareness needed to make responsible choices. The accompanying CD-ROM contains all the exercises allowing therapists to customize them to fit their needs"--Provided by publisher.
Includes bibliographical references (p. 121-127).
Keywords: Substance abuse -- Treatment; Substance-Related Disorders -- therapy; Behavior, Addictive -- therapy; Counseling -- methods; Psychotherapy, Group -- methods